Non-additive effects of litter mixtures on decomposition of leaf litters in a Mediterranean maquis - Marco, Anna; Meola, Angela; Maisto, Giulia; Giordano, Maria; Virzo De Santo, Amalia (Plant and Soil, 2011)
Many studies across a range of ecosystems have shown that decomposition in mixed litter is not predictable from single-species results due to synergistic or antagonistic interactions. Some studies also reveal that species composition and relative abundance may be more important than just richness in driving non-additive effects. Most studies on litter decomposition in Mediterranean maquis, an highdiversity shrubby ecosystem, have dealt exclusively with single species. In this study we investigated, at the individual-litter level, as well as at the littermixture level, the effect of litter mixing on decomposition of 3-species litter assemblages with different relative abundance of the component litters; we set up two types of litter assemblages that reflected the heterogeneity of bush cover in the inner maquis and at the edge maquis/gaps, as related to the leaf traits, i.e. sclerophylly vs mesophylly. We measured mass loss, decay of lignin, cellulose and ADSS (acid detergent soluble substances) and fungal mycelium ingrowth. The results show that over a 403-day incubation period, the decomposition of individual litters in mixtures deviated from that of monospecific litters and had different directions. In litter mixtures of the sclerophylls Phillyrea angustifolia and Pistacea lentiscus with the mesophyll Cistus, decomposition was lower than expected (antagonistic effect); in the mixtures of litters with similar physical structure (Ph. angustifolia and P. lentiscus with Quercus ilex) decomposition was faster than expected (synergistic effect). When considering the different decomposition phases, both negative and positive effects occurred in Quercus mixtures depending on the phase of decomposition. In both types of 3-species litter assemblages the greatest effect occurred in uneven mixtures rather than in even mixtures. Our results show that species composition drives the direction whilst the decomposability and the relative abundance drive the magnitude of non-additive effects of litter mixing on decomposition.
Keywords: decomposition phases; fungal mycelium; individual litter in mixture; litter evenness; monospecific litter; sclerophylls vs mesophylls

Nutrient dynamics in litter mixtures of four Mediterranean maquis species decomposing in situ - Maisto, Giulia; De Marco, Anna; Meola, Angela; Sessa, Ludovica; Virzo De Santo, Amalia (Soil Biology and Biochemistry, 2011)
In natural conditions, litters shed from different species become mixed with each other, and decompose together. Most studies deal with decomposition of individual species; few studies investigate the inﬂuence of litter mixing on decomposition and nutrient dynamics; the results are contradictory as positive, negative, or no effect, of litter mixing have been observed. In this study we test the hypothesis: i) that litter mixing in the Mediterranean maquis, a nutrient poor, high diversity ecosystem, produces non-additive effects on nutrient dynamics; ii) that the effects vary with the composition in species of the mixture and with the relative amount of the species component the mixture. Two types of 3-species mixtures were set up; one contained three sclerophylls, Phillyrea angustifolia, Pistacia lentiscus and Quercus ilex; the other contained the ﬁrst two species with the mesophyll Cistus. Litterbags, containing monospeciﬁc litters and even and uneven mixtures, were incubated under natural condition in situ; even mixtures had the 3 species in equal proportion, whereas uneven mixtures had one of the species as dominant (50%) and the other two species in equal proportion (25%:25%). Litterbags were retrieved after 92, 188 and 403 days; litters from the mixtures were separately analyzed for mass loss and content of nitrogen (N), potassium (K), sodium (Na), calcium (Ca), magnesium (Mg), manganese (Mn), iron (Fe), copper (Cu), and zinc (Zn). Results indicate that mixing inﬂuences the dynamics of N, Mn, Ca, Mg, Fe, Cu and Zn, but scarcely affects the dynamics of K and Na. The comparison of observed to expected values for changes of nutrients in litterbags indicates the occurrence of non-additive effects of litter mixing on movements of N, Fe, Cu, and Zn to or from the litterbags containing the mixtures. The effects depend on the composition in species of the mixture, whereas the relative amount of the species component the mixture is not relevant.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Interactions among litters; Lignin; litter decomposition; Manganese; Non-additive effects of litter mixing